(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Within the master’s work "Characterization of the Solanum tuberosum and Solanum phureja potato production system in the departments of Norte de Santander and Santander" two instruments were applied at different times to focus groups of farmers from the two departments, the first, adapted the Framework for the Evaluation of Management Systems Incorporating Sustainability Indicators, and had 21 indicators, weighted on a scale from 0 to 10, to evaluate 7 variables: family nucleus, organization of economic activities, good agricultural practices, diversity and synergies, infrastructure and resources, services, technology transfer. The second corresponded to an analysis of strengths, weaknesses, opportunities and threats SWOT for potato production. Likewise, a semi-structured interview was applied to key actors (farmers and technical assistants) to know their perceptions about access and relevance of potato research. The results show differences for the sustainability of production, finding the non-application of good agricultural practices as the most limiting aspects, and diversity and productive synergies as an aspect of strength. The SWOT analysis reveals typical characteristics and problems of small farmers, but the application of Law 1930 of 2018 on the delimitation of moors stands out as a threat, considering the need to become visible as protectors of said ecosystem. Finally, according to the perception of farmers and technical assistants, potato research is relevant in technical agronomic aspects, but there are difficulties in accessing its results.